Elastic deformation impact on trihybrid nanofluid flow through different geometries with the combine effects of electrophoresis and thermophoresis - Munawar Abbas; A. Al-Zubaidi; Abdullah A. Faqihi; Ilyas Khan; A.F. Aljohani; Abdoalrahman S.A. Ome; Ahmed M. Gala (Ain Shams Engineering Journal)
This study inspected the impacts of thermophoresis and electrophoresis on the rate of aerosol particle deposition through cone, plate, wedge geometries in a Marangoni convective flow. The proposed mathematical model becomes more innovative by taking into account the effects of elastic deformation, variable thermal conductivity and mixed convection. It uses a trihybrid nanofluid composed of water-based fluid, Silver (Ag), Titanium dioxide (TiO2), and Magnesium oxide (Mgo) nanoparticles. One important area of use is in the design and improvement of trihybrid nanofluid-based materials with specialized thermal, electrical, and mechanical properties. Improvements in heat transmission in microfluidic and nanofluidic devices are critical for chemical reactions, electronics cooling, and biological applications. Improved materials processing methods, precise drug administration mechanisms, and more effective cooling systems can all result from an understanding of the interactions between fluid flow, elastic deformation, and nanoparticle dynamics under the impact of electrical and temperature gradients. The equations corresponding to the suggested PDEs (particle differential equations) are converted into ODEs (ordinary differential equations) by choosing suitable similarity transformation. The semi-analytical technique HAM (Homotopy analysis method) is executed to drive the solution of the proposed problem. When the values of the elastic deformation parameter increase, the thermal and velocity profiles decline. With higher values of electrophoretic parameter, the concentration profile becomes augmented.